Speaking for the Unheard: A quantitative examination of the marginalization of the scholarship of LGBTQ+ issues in the Global South - Lendvai, Gergely Ferenc (KOME, 2025)
This study investigates the impact of restrictive environments on LGBTQ+ scholarship in the Global South, focusing on publication patterns, research themes and the role of international collaboration in enhancing research visibility. Analysis was conducted on data from 57 countries over a 30-year period (1993–2023) from Scopus using bibliometric and network analyses to explore the barriers scholars face when addressing LGBTQ+ issues in regions where these topics are socially or politically censored. The findings reveal a steady increase in LGBTQ+ research from the Global South, with a strong focus on identity and health-related themes, while political and legal discussions remain underrepresented. Collaborations with Global North scholars significantly boost visibility and citation impact, although issues of equitable power sharing within these collaborations persist. The study concludes that international partnerships, while crucial in amplifying marginalised voices, must ensure equitable contributions from scholars in the Global South to promote a more inclusive and balanced body of knowledge.